Perlindungan Hukum Melalui Pendampingan Psikolog Bagi Korban Kekerasan Dalam Rumah Tangga Dalam Kerangka Undang-Undang Penghapusan Kekerasan dalam Rumah Tangga Nomor 23 Tahun 2004 Dan Hak Konstitusional Atas Kesehatan - Putri, Putu Siska Rudiana; Wulandari, Ni Gusti Agung Ayu Mas Tri (Consensus : Jurnal Ilmu Hukum, 2025)
Domestic violence is a serious problem in Indonesia, causing not only physical injuries but also leaving deep psychological scars on victims. Domestic violence can be experienced by women, men, and children. The mental recovery of victims is an important aspect that must be guaranteed by the state as part of the constitutional right to health. This article aims to examine the role of psychological counseling as a form of legal protection for victims of domestic violence within the framework of Law No. 23 of 2004 on the Elimination of Domestic Violence, as well as its relation to the fulfillment of the right to mental health. The study used a normative legal method with a legislative and conceptual approach. The results of the analysis show that psychological assistance is an integral part of the legal protection of victims as stipulated in the Law on the Elimination of Domestic Violence. This confirms that the recovery of victims is the responsibility of the state, while the 1945 Constitution and the Health Law guarantee the right of every citizen to health, including mental health. Thus, psychological counseling services cannot be viewed as an additional option, but rather as a legal instrument that must be provided in order to fulfill the human rights of victims. In conclusion, the fulfillment of the right to mental health through psychological counseling for victims of domestic violence is a tangible form of legal protection that needs to be strengthened with more comprehensivepolicies and regulations.